Atitudes lingüísticas de alunos de escolas públicas de Juiz de Fora MG - Cyranka, Lúcia Furtado de Mendonça (2007)
A linguistic attitudes test (LAMBERT et. al, 1960) was proposed to the students of the 8th. grade of five public schools in Juiz de Fora MG. It aims at investigating the students rating in three Brazilian dialects in the rural-urban continuum. A private school was also included because it could be a good contrasting parameter in this investigation. The results of the attitude test showed a strong identification of all students with the rurban variety, which is in the middle of the continuum. There was no difference between the ratings of the students of the public schools and the private one. The students also established a clear connection between the urban/standard variety and the power dimension, but the solidarity dimension is linked to the rural and the rurban one. This demonstrated on the one hand, the existence of covert prestige and, one the other hand, how distant the students are from the urban/standard variety. Rural students held negative attitudes toward the standard variety and this caused very important pedagogic consequences, because they carry on to school their cultural references which ought to be respected in their linguistic development, in the acquisition of this standard variety during the school activities. One test of beliefs (direct measure), was also used to verify whether the students beliefs are connected with the teacher s ones, and whether students difficulties in developing their abilities in standard language uses are connected with the teacher s beliefs. This test was answered by the teachers of the same schools and by students of the last grade of the Curso de Letras of UFJF. The result pointed out that the students are in conflict between the recognition of their linguistic variety (attitude test) and the statement that they can t speak well (belief test): students of the 8th. grade demonstrate insecurity in using their mother tongue and they are attached to false beliefs, as that they have to study grammar rules and orthography to overcome these difficulties. This is harmful to their self-esteem and increases the linguistic prejudices, sometimes not in accordance with their own language uses: they think that speaking is less correct than writing. It points to the insufficiency of school activities with the oral language. The students expectation, however, is that the school can help them overcome these difficulties. One important issue to be pointed out is the teachers belief that to speak well ones has to study grammar, 40,9% think that this is true. This persistent position of the teachers probably influences the increasing negative attitudes of the students identification with the standard language variety. This could be minimized by the culturally responsive pedagogy to reduce the asymmetric interaction, to reduce the distance between the teacher s variety prestige and the students variety. In short, the results point out the existence of a system of beliefs, that many of them are false beliefs, and that they influence the beliefs and the students linguistic attitudes. This influence increases the students difficulties in developing their abilities in the standard dialect use. But it seems that this situation is changing among the students of the last grade of the Curso de Letras